Biological Function of PD-L2 and Correlation With Overall Survival in Type II Endometrial Cancer - Marinelli, Oliviero; Annibali, Daniela; Morelli, Maria Beatrice; Zeppa, Laura; Tuyaerts, Sandra; Aguzzi, Cristina; Amantini, Consuelo; Maggi, Federica; Ferretti, Benedetta; Santoni, Giorgio; Amant, Frédéric; Nabissi, Massimo (Frontiers in Oncology, 2020)
In cancer, up-regulation of co-inhibitory B7 ligands has been associated with immune evasion. So far, anti-programmed death-1 (PD-1) and anti-PD-ligand 1 (PD-L1) antibodies have been used in immuno-oncology, with promising outcomes; however, it is still needed to identify other markers, especially for endometrial cancer (EC). EC is a gynaecological malignancy historically classified into two types, type I, with mostly oestrogen-dependent endometrioid diseases, and the most aggressive type II, including mainly oestrogen-independent and non-endometrioid tumors. PD ligand-2 (PD-L2) is known as the second ligand of the PD-1 receptor, and upon its binding contributes to T-cell exhaustion. Up to now, very few information are available about PD-L2 in cancers and no data have been reported for EC. The aim of this work was to characterize the PD-L1 and PD-L2 ligands expression profile in EC cell lines, focusing the attention on the biological role of PD-L2 and its prognostic impact in human type II EC biopsies. Using in silico analysis of TCGA data, we performed a molecular profiling in a cohort of 506 patients, both type I and II, and PD-1 ligands expression was also analysed in different primary human EC cell lines. Moreover, PD-L2 staining was evaluated in a cohort of human type II EC samples, and correlated with the Overall Survival (OS), Progression-Free Survival (PFS) and additional clinicopathological data. As emerged from the in silico analysis, PD-L2 was more expressed than PD-L1 in EC cell lines. PD-L2 was found highly expressed in 64.44% of tumor specimens, predominantly in the serous subtype, in both stromal and epithelial components, while in peritumoral and normal tissues it was predominantly moderate or low. In vitro, we investigated the cell autonomous role of PD-L2 in controlling cell survival, migration and chemoresistance.